Extremity soft tissue sarcoma with multiple primary malignancies – Characteristics and outcome. Issue 4 (April 2016) - Lopez-Oliva, C.L.L.; Yun, J.Y.; Kim, H.-S.; Han, I.
Abstract: Background: Understanding the incidence and characteristics of multiple primary malignancies (MPM) has implications for guiding appropriate treatment and surveillance of extremity soft tissue sarcoma (STS). Objectives: We sought to examine the incidence of MPM in STS (MPM-STS), and compare their clinicopathologic characteristics and survival to those with STS only. Methods: 585 patients who underwent surgery for extremity STS were reviewed. Logistic regression analyses to identify factors contributing to the development of MPMs and a 1:2 matched case–control analysis to compare survival outcome were performed. Results: Of the 585 patients analyzed, 34 (6%) with MPM were identified. On univariate logistic regression analysis, older age (>49 years) at STS diagnosis (p = 0.008) and histologic types of undifferentiated pleomorphic sarcoma or myxofibrosarcoma (p = 0.033) were significant. In multivariate analysis, only older age at STS diagnosis remained significant (OR = 2.5, p = 0.029). Cancer-specific survival of the MPM-STS group was significantly lower than that of the STS-only group (p = 0.031). However, there was no significant difference in STS-specific survival between the two groups (p = 0.208). Conclusion: Our study suggests that MPM is not uncommon in extremity STS and older age at STS diagnosis is associated with risk of MPM. Prognosis of STS in the MPM-STS group seems similar to that of the STS-only group.